INCOME TAX AS A COMPONENT OF FINANCIAL CAPACITY OF NEW AMALGAMATED COMMUNITIES IN UKRAINE - Нікіфоров, Петро Опанасович; Людмила, Павлович (Wydawnictwo Wyższej Szkoły Gospodarki Krajowej w Kutnie, 2020)
The influence of the state tax mechanism on the formation of the income part of communities is substantiated. It is noted that the decentralization reform largely shifts the provision of social services and ensuring the quality of life of its citizens to local governments. It is established that on the way to achieving the independence of territorial communities there are obstacles at the national and local levels. In order to establish a correlation between the effectiveness of the tax mechanism of regulating the income of the population and the financial capacity of local communities, the regulatory framework and taxation practices in EU countries were studied. The budget-forming role of personal income taxes in the formation of local budget revenues has been established. The shortcomings of the modern tax mechanism for regulating the income of the population have been identified and directions for its improvement have been proposed.
Надходження від оподаткування доходів населення як основа фінансової спроможності об’єднаних територіальних громад України
Keywords: state regulation; tax capacity; personal income tax; household income; tax mechanism